Anti-inflammatory choline based ionic liquids: Insights into their lipophilicity, solubility and toxicity parametrites - Araújo, ANDRÉ (2018)
The impact on in vivo efficacy and safety of two novel ionic liquids based on the association of choline with nonsteroidal anti-inflammatory drugs, ketoprofen and naproxen forming IL-APIs, was evaluated. Their lipophilicity, solubility and toxicity were assessed aiming the illustration of the pharmaceutical profile and potential toxic impact. Partition coefficientwas determined usingmicelles of hexadecylphosphocholine and UV–Vis derivative spectroscopy. Additionally, solubility in phosphate buffer pH 7.4 wasmeasured using amodified shake flaskmethod and UV–Vis spectroscopy as detection technique. Ultimately, toxicity was considered resorting to a fully automated cytochrome c oxidase assay based onmicrofluidics. The obtained results demonstrated that the IL-APIs' drug format has the ability to interact with biological membranes and also improves solubility up to 58 times. Moreover, it was evidenced that, although being a nutrient, choline influences the IL-APIs' toxicity. The studied anti-inflammatory IL-APIs exhibited promising properties regarding their incorporation in pharmaceutical formulations.